2016
DOI: 10.1007/s10534-016-9948-y
|View full text |Cite
|
Sign up to set email alerts
|

Asthma as a disruption in iron homeostasis

Abstract: Over several decades, asthma has evolved from being recognized as a single disease to include a diverse group of phenotypes with dissimilar natural histories, pathophysiologies, responses to treatment, and distinctive molecular pathways. With the application of Occam's razor to asthma, it is proposed that there is one cause underlying the numerous phenotypes of this disease and that the responsible molecular pathway is a deficiency of iron in the lung tissues. This deficiency can be either absolute (e.g. asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 356 publications
0
10
0
Order By: Relevance
“…Asthma and COPD belong to the subgroup of obstructive pulmonary diseases [158]. The potential role of a disrupted iron homeostasis in asthma was reviewed in great detail recently [159]. Briefly, the author reported profound evidence of disturbed iron homeostasis in asthma by systematically evaluating the known demographic (e.g., ethnicity), physiologic (e.g., exercise), and pathologic (e.g., infections) asthma determinants in the context of iron availability and concluded a setting of absolute or functional iron deficiency in asthma, which may have therapeutic implications in the future.…”
Section: Linking Lung-related Diseases To Disrupted Lung Iron Homementioning
confidence: 99%
“…Asthma and COPD belong to the subgroup of obstructive pulmonary diseases [158]. The potential role of a disrupted iron homeostasis in asthma was reviewed in great detail recently [159]. Briefly, the author reported profound evidence of disturbed iron homeostasis in asthma by systematically evaluating the known demographic (e.g., ethnicity), physiologic (e.g., exercise), and pathologic (e.g., infections) asthma determinants in the context of iron availability and concluded a setting of absolute or functional iron deficiency in asthma, which may have therapeutic implications in the future.…”
Section: Linking Lung-related Diseases To Disrupted Lung Iron Homementioning
confidence: 99%
“…Preservation of iron homeostasis is of extreme importance for the respiratory physiology and pathophysiology as well as local iron deficit or accumulation may result in certain respiratory function impairment Forced Expiratory Volume in one second (FEV1,) Forced Vital Capacity (FVC), FEV1/FCV and Peak Expiratory Flow (PEF). [12,[13][14][15][16][17].It had been shown that iron-supplemented diet had markedly decreased allergen-induced airway hyperreactivity, by decreasing mast cell activation [3,4,[17][18][19]. Identification of further treatments that could preclude or decline the rigorousness of asthma would offer a chief progress in clinical attention of patients with allergen-started asthma [20,21].…”
Section: Issue 2decsmber 2019mentioning
confidence: 99%
“…More than 80% of the patients with asthma had concomitant rhinitis, and 10–40% of the patients with rhinitis had concomitant asthma,22 which lends credence to the concept of “one airway, one disease” 3. It has also been shown that urticaria is a common co-morbidity of asthma,23 and also has significant correlation with AR and asthma 24. However, the increased risk of CU in different age groups was not consistent.…”
Section: Discussionmentioning
confidence: 99%